Does trunk range of motion during sitting Para cross-country skiing differ between classes? - Severin, A. C.; Baumgart, J. K.; Kocbach, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In sitting Para cross-country (XC) skiing, athletes compete in a seated position and thus rely predominantly on their arms and trunk for propulsion [1]. Double poling at higher work rates requires increased trunk motions [2], and it is likely that the trunk function of Para sit-skiers will influence their ability to produce high power output [3] and speeds. The classification of sitting XC-skiers is based on clinical trunk function tests, and athletes with higher trunk function are often allocated to higher classes. However, it is difficult to accurately estimate the functional trunk range of motion (ROM) of an athlete during sit-skiing based on these assessments. Modern inertial measurement unit (IMU) technology allows the estimation of the trunk ROM during on-snow competitions. This study therefore aimed at comparing the trunk ROM between classes of sitting para-XC skiers during competition.